Effectiveness of a bite-sized web-based intervention to improve healthcare worker wellbeing: A randomized clinical trial of WISER - Sexton, J. Bryan; Adair, Kathryn C.; Cui, Xin; Tawfik, Daniel S.; Profit, Jochen (Frontiers in Public Health, 2022)
Importance: Problems with healthcare worker (HCW) well-being are widespread and associated with detrimental consequences for the workforce, organizations, and patients. Objective: This study tested the effectiveness of the Web-based Implementation for the Science of Enhancing Resilience (WISER) intervention, a positive psychology program, to improve six dimensions of HCW well-being. Design: We conducted a randomized controlled trial between April 1st 2018 and July 22nd 2019. Cohort 1 received WISER daily for 10 days. Cohort 2 acted as a waitlist control before receiving WISER. Setting: Web-based intervention for employed HCWs across the US. Participants: Eligibility criteria were ≥18 years old and a HCW. Participants were randomized to start the intervention or serve as a waitlist control for 14 days before starting the intervention. Interventions: Cohorts received links via 10 texts exposing them to introductory videos and positive psychology exercises (3 Good Things, Cultivating Awe, Random Acts of Kindness, Cultivating Relationships, and Gratitude Letter). Main Outcomes and Measures: The primary outcome was emotional exhaustion, secondary outcomes were depressive symptoms, work-life integration, happiness, emotional thriving and emotional recovery. All outcomes were assessed at baseline, 1-week post (primary endpoint), and 1-month, 6-month and 12-month post-intervention. Six items evaluated participant experience with WISER. The analysis employed mixed-effects models. Results: In cohorts 1 and 2 respectively, 241 and 241 initiated WISER, and 178(74%) and 186(77%) completed the 6-month follow-up. Cohort populations were similar at baseline, mostly female (81;76%) and nurses (34;32%) or physicians (22;23%), with 1-10 years of experience in their current position (54;52%). Relative to control, WISER significantly improved depressive symptoms (-7.5(95%CI:-11.0, -4.0),p<.001), work-life integration (6.5(95%CI:4.1, 8.9),p<.001), happiness (5.7(95%CI:3.0, 8.4),p<.001), emotional thriving (6.4(95%CI:2.5, 10.3),p=.001), and emotional recovery (5.3(95%CI:1.7, 8.9),p=.004), but not emotional exhaustion (-3.7(95%CI:-8.2,0.8),p=.11) at 1 week. Combined cohort results at 1, 6, and 12-months showed that all six well-being outcomes were significantly improved relative to baseline, p<.05. Favorable impressions of WISER were reported by 87% of participants at the 6-month post-assessment. Conclusions: WISER improved HCW depressive symptoms, work-life integration, happiness, emotional thriving, and emotional recovery. Improvements in all HCW well-being outcomes endured at the 1, 6 and 12-month follow-up. HCW impressions of WISER were positive.